2014
DOI: 10.1007/s10067-013-2477-y
|View full text |Cite
|
Sign up to set email alerts
|

Pain threshold and intensity in rheumatic patients: correlations with the Hamilton Depression Rating scale

Abstract: Individuals suffering from chronic pain are frequently affected by depression, which in turn increases the risk of developing chronic pain over time. This study aims to investigate the relationship between depression and pain intensity and threshold in a group of rheumatic patients compared to healthy subjects. One hundred twenty-four individuals of whom 50 were affected by rheumatoid arthritis (RA), 23 by psoriatic arthritis (PsA), 23 by ankylosing spondylitis (AS), and 28 age-matched controls without chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…Contributions from central sensitization to generalized pain in RA and OA are well documented (6,7,14,41). Previous studies of pain mechanisms in PsA are scarce and include a few studies that have demonstrated lowered pain pressure thresholds in PsA versus healthy controls (42) and high frequencies of mixed/neuropathic pain features in PsA according to the PDQ score, similar to our findings (3). Other studies have mainly focused on the worst-end spectrum of central sensitization, i.e., fibromyalgia.…”
Section: Discussionsupporting
confidence: 86%
“…Contributions from central sensitization to generalized pain in RA and OA are well documented (6,7,14,41). Previous studies of pain mechanisms in PsA are scarce and include a few studies that have demonstrated lowered pain pressure thresholds in PsA versus healthy controls (42) and high frequencies of mixed/neuropathic pain features in PsA according to the PDQ score, similar to our findings (3). Other studies have mainly focused on the worst-end spectrum of central sensitization, i.e., fibromyalgia.…”
Section: Discussionsupporting
confidence: 86%
“…BRAF-MDQ Physical and Living) suggesting that pain intensity may influence the energy and the ability to cope, physically and socially. Previous studies show a weak association between pain threshold and VAS pain in persons with rheumatic diseases and chronic pain (29,30), while stronger association has been observed between pain threshold and depression (30), both of which relate to the central nervous system. This highlights the multifaceted nature of pain in RA, which can be influenced by peripheral and central pain sensitization beyond inflammation (10,26).…”
Section: Discussionmentioning
confidence: 90%
“…However, as we neither tested pain sensitivity locally on the knee or at more remote areas (e.g., upper extremity), it is not possible to determine if exercise therapy reduces the peripheral input from the knee to provide local desensitization, or if more universal adaptations in the central nervous system have occurred yielding a general desensitization. Exercise is also likely to cause changes in psychological variables, such as depression and quality of life (), that are associated with pain sensitivity (). In the present study these factors were unfortunately not assessed, and it is possible that the reduced pain sensitivity after exercise may also be mediated through improvements in psychological well‐being.…”
Section: Discussionmentioning
confidence: 99%